IMPLEMENTASI POLA ARGUMEN TOULMIN DALAM MENULIS TEKS ARGUMENTASI SISWA KELAS XI SMKN 9 MUARO JAMBI - Dian Amalia Sari; Agus Setyonegoro; Priyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the Toulmin argument pattern in teaching argumentative writing to eleventh-grade students at SMK Negeri 9 Muaro Jambi. This research employed a qualitative approach with an intrinsic case study design. The data were collected through observation, interviews, and documentation. The sources of data included one Indonesian language teacher and 27 students of class XI in the Light Vehicle Engineering program. The data were analyzed descriptively through the stages of data organization, reduction, categorization, interpretation, and narrative presentation. The results showed that the implementation of the Toulmin argument pattern had a positive impact on students’ ability to write argumentative texts. The learning process became more structured and systematic as students were guided to construct the elements of argument, namely claim, data, warrant, backing, qualifier, and rebuttal. Based on the analysis of students’ argumentative texts, 80% of the students were categorized as very good and 20% as good. These findings indicate that the Toulmin argument pattern is effective in improving the structure of arguments as well as students’ logical and critical thinking skills in argumentative writing.